Prompt and non-prompt J/[psi] production and nuclear modification at mid-rapidity in p-Pb collisions at √sNN=5.02 TeV - Acharya, Shreyasi; Angelov, Venelin; Arslandok, Mesut; Danisch, Meike; Deisting, Alexander; Feuillard, Victor; Glässel, Peter; Kim, Jiyoung; Köhler, Markus Konrad; Klewin, Sebastian; Leardini, Lucia; Mercado Pérez, Jorge; et al. (The European physical journal. C, Particles and fields, 2018)
A measurement of beauty hadron production at mid-rapidity in proton-lead collisions at a nucleon-nucleon centre-of-mass energy sNN−−−√=5.02sNN=5.02\sqrt{s_\text {NN}}=5.02 TeV is presented. The semi-inclusive decay channel of beauty hadrons into J/ψJ/ψ\hbox {J}/\psi is considered, where the J/ψJ/ψ\hbox {J}/\psi mesons are reconstructed in the dielectron decay channel at mid-rapidity down to transverse momenta of 1.3 GeV/c. The bb¯bb¯\hbox {b}\bar{\hbox {b}} production cross section at mid-rapidity, dσbb¯/dydσbb¯/dy\hbox {d}\sigma _{\hbox {b}\bar{\hbox {b}}}/\hbox {d}y, and the total cross section extrapolated over full phase space, σbb¯σbb¯\sigma _{\text {b}\bar{\text {b}}}, are obtained. This measurement is combined with results on inclusive J/ψJ/ψ\hbox {J}/\psi production to determine the prompt J/ψJ/ψ\hbox {J}/\psi cross sections. The results in p-Pb collisions are then scaled to expectations from pp collisions at the same centre-of-mass energy to derive the nuclear modification factor RpPbRpPbR_{\text {pPb}}, and compared to models to study possible nuclear modifications of the production induced by cold nuclear matter effects. RpPbRpPbR_{\text {pPb}} is found to be smaller than unity at low pTpTp_{\mathrm{T}} for both J/ψJ/ψ\hbox {J}/\psi coming from beauty hadron decays and prompt J/ψJ/ψ\hbox {J}/\psi .